Passengers’ choice for full-service carrier airlines / Yasmin Kaisah Ahmad Zolkifli - Ahmad Zolkifli, Yasmin Kaisah (Faculty of Business and Management, 2019)
Passengers travelling by air keep increasing each year and it was forecast that there will be 30 million of air passengers by 2020. This shows that the usage of airline operators will increase and at the same time there will also be an intense competition between airline operators. Thus, the airline operators need to know what are the factors that influencing the passengers’ choice for airlines in order to tackle this problem. The purpose of the research study is to investigate the factors influencing passengers’ choice for full-service carrier airline. The independent variables used are price, brand image, in-flight meals, marketing communication and product. The method used in conducting this research study is by distributing questionnaires a total of 384 respondents as sample size were taken. The results of the research study show that brand image is the most dominant factors influencing passengers’ choice for full-service carrier airline and all of the independent variables are significant except for price.